Work of Breathing into Snow in the Presence versus Absence of an Artificial Air Pocket Affects Hypoxia and Hypercapnia of a Victim Covered with Avalanche Snow: A Randomized Double Blind Crossover Study - Roubík, Karel; Sieger, Ladislav; Sykora, Karel (PloS one, 2015)
Presence of an air pocket and its size play an important role in survival of victims buried in the avalanche snow. Even small air pockets facilitate breathing. We hypothesize that the size of the air pocket significantly affects the airflow resistance and work of breathing. The aims of the study are (1) to investigate the effect of the presence of an air pocket on gas exchange and work of breathing in subjects breathing into the simulated avalanche snow and (2) to test whether it is possible to breathe with no air pocket. The prospective interventional double-blinded study involved 12 male volunteers, from which 10 completed the whole protocol. Each volunteer underwent two phases of the experiment in a random order: phase "AP"--breathing into the snow with a one-liter air pocket, and phase "NP"--breathing into the snow with no air pocket. Physiological parameters, fractions of oxygen and carbon dioxide in the airways and work of breathing expressed as pressure-time product were recorded continuously. The main finding of the study is that it is possible to breath in the avalanche snow even with no air pocket (0 L volume), but breathing under this condition is associated with significantly increased work of breathing. The significant differences were initially observed for end-tidal values of the respiratory gases (EtO2 and EtCO2) and peripheral oxygen saturation (SpO2) between AP and NP phases, whereas significant differences in inspiratory fractions occurred much later (for FIO2) or never (for FICO2). The limiting factor in no air pocket conditions is excessive increase in work of breathing that induces increase in metabolism accompanied by higher oxygen consumption and carbon dioxide production. The presence of even a small air pocket reduces significantly the work of breathing.
Keywords: hyperkapnie; dospělí; Healthy Volunteers; Hypoxia; klinické křížové studie; dechový objem; dechová práce; monitorování fyziologických funkcí; Asphyxia; Adult; laviny; Monitoring, Physiologic; zdraví dobrovolníci pro lékařské studie; Inspiratory Reserve Volume; lidé; dvojitá slepá metoda; Cross-Over Studies; Hypercapnia; Carbon Dioxide; Tidal Volume; hypoxie; Snow; inspirační rezervní objem; Double-Blind Method; Male; Oxygen; Work of Breathing; oxid uhličitý; Disasters; katastrofy; mužské pohlaví; sníh; asfyxie; Avalanches; kyslík; Humans